Pentingnya pendidikan kewirausahaan untuk generasi z agar dapat menyiapkan diri menjadi start up - Ni Made Shinta Adhella (Journal Science Innovation and Technology (SINTECH), 2021)
This paper aims to inform that entrepreneurship education is very important for Generation Z because many new businesses or start-ups are called start-ups. This entrepreneurship education can be a provision for young people who will enter the world of work which is actually not easy and full of competition, therefore entrepreneurship education is very important and teachers need to instill the soul to become entrepreneurs because being an entrepreneur can provide jobs for students. The number of job seekers is increasing every year. In fact, in February 2020 there were 2.92 million job seekers in Indonesia, which were divided into 2 categories, the first being 1.73 million workforce and 1.19 million non-laborers.